A single-institution experience with hydrostatic reduction for childhood intussusception: a preliminary report. Issue 2 (April 2016) - Elebute, Olumide A.; Ademuyiwa, Adesoji O.; Idiodi-Thomas, Hestia O.A.; Alakaloko, Felix M.; Seyi-Olajide, Justina O.; Bode, Christopher O.
Abstract : Background/purpose: Hydrostatic reduction for intussusception has the benefit of achieving reduction without the need for general anaesthesia or surgery and the possible attendant complications. This has made it the most popular interventional modality in many centres today. Hydrostatic reduction was added to our armamentarium in the treatment of childhood intussusception recently and this report represents our initial experience. Methods: This study is a prospective review of all cases of intussusception that presented at the Emergency Department at the Lagos University Teaching Hospital between February 2012 and May 2014. Eligibility for hydrostatic reduction was based on internationally recognized criteria, which included absence of peritonitis and shock. Data were analyzed using the statistical package for social sciences (version 20). The χ 2 -test was used to compare categorical variables, and a P value of 0.05 was considered significant. Results: A total of 66 patients were seen within the study period. Thirty-eight were male (57.6%) and 28 were female (42.4%). The age range was 3–84 months and the mean age was 12.0±30.8 months. Twenty-six patients (39.4%) underwent hydrostatic reduction, of which 11 (42.3%) were successful. There was a correlation between the duration of symptoms and successful hydrostatic reduction ( P <0.05), with five of the 11 (45.5%) presenting within 24 h of symptoms. Conclusion: Although less than half of the patients presenting with childhood intussusception were eligible for hydrostatic reduction, the method remains a feasible option in our environment in spite of late presentation by most of our patients. The duration of presenting symptoms was the most important determinant of successful hydrostatic reduction.